ANALYSIS OF THE INFLUENCE OF TARIFF POLICY, PASSENGER VOLUME, AND FLIGHT CONNECTIVITY ON PASSENGER SERVICE CHARGE (PSC) REVENUE AT FRANS KAISIEPO BIAK INTERNATIONAL AIRPORT POST COVID-19 PANDEMIC - Muhammad Bagas Prawira; Abdul Mukti Soma (RADJA PUBLIKA, 2026)
This study aims to analyze the influence of PSC tariff policy, passenger volume, and flight connectivity on Passenger Service Charge (PSC) revenue at Frans Kaisiepo International Airport during the 2018–2025 post-COVID-19 recovery period. A quantitative explanatory approach was applied using secondary time-series data obtained from official airport and government reports. The data were analyzed through multiple linear regression with classical assumption testing using IBM SPSS Statistics 26. The results indicate that PSC tariff policy has a significant positive effect on PSC revenue, while passenger volume shows a positive but statistically weaker effect at the 5% significance level. Flight connectivity does not have a significant direct effect on PSC revenue. Simultaneously, the independent variables significantly explain variations in PSC revenue with a high coefficient of determination. The study is limited by the small number of annual observations and the structural relationship between tariff and passenger volume. Future research is recommended to use higher-frequency data and apply advanced time-series techniques to enhance robustness and generalizability.